Parental Time Restrictions and the Cost of Children: Insights from a Survey among Mothers - Melanie Borah; Andreas Knabe; Kevin Pahlke (Center for Economic Studies and ifo Institute (CESifo), 2018)
In this paper, we provide estimates of the subjectively perceived cost of children depending on the extent of parental time restrictions. Building on a study by Koulovatianos et al. (2009) that introduces a novel way of using subjective income evaluation data for such estimations, we conduct a refined version of the underlying survey, focusing on young women with children in Germany. Our study confirms that the monetary cost of children is substantial and increases with parental nonmarket time restrictions. The loss in the material living standard associated with supplying time to the labor market is sizeable for families with children.
Keywords: I32; J13; J22; 330; child cost; equivalence scales; full-time employment; subjective income evaluations